1999
DOI: 10.1038/5597
|View full text |Cite
|
Sign up to set email alerts
|

A co-stimulatory signal through ICAM-β2 integrin-binding potentiates neutrophil phagocytosis

Abstract: The beta2 integrin LFA-1 (lymphocyte function associated antigen; CD11a/CD18) is the common ligand for the intercellular adhesion molecules (ICAMs). Integrins support cell function by providing co-stimulatory second signals that are a precondition for full cell activation first described for ICAM-1-binding to LFA-1 in lymphocytes. Integrins can also serve to activate functions associated with distinct subunits of other integrins. In addition to LFA-1, neutrophils express the beta2 integrin Mac-1 (CD11b/CD18; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 23 publications
0
57
0
1
Order By: Relevance
“…This response, stimulated by chemotactic factors, was markedly augmented by CD11b-dependent adhesion via the interaction of CD11b with ICAM-1 expressed on the endothelial cell surface (22,29). CD11b was also shown to be associated with components of the NADPH complex, p47 phox and gp91 phox , after TNF-␣ challenge (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…This response, stimulated by chemotactic factors, was markedly augmented by CD11b-dependent adhesion via the interaction of CD11b with ICAM-1 expressed on the endothelial cell surface (22,29). CD11b was also shown to be associated with components of the NADPH complex, p47 phox and gp91 phox , after TNF-␣ challenge (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that staphylococci and streptococci differ in their sensitivity to phagocytosis, depending on the expression of neutrophil surface receptors. 26 Hence, the impact of zinc deficiency on phagocytosis by monocytes may also vary with the bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…Airway response to bacterial pathogens is modulated by increased expression of ICAM-1 [66,134]. Interaction of ICAM-1 with CD11/CD18 on leukocytes is determinant for leukocyte adhesion to airway epithelial cells [90,135] and decreased ICAM-1 expression or function may result in impaired leukocyte recruitment and/or antimicrobial activity [134,136,137]. Therefore, the current evidence suggests that airway epithelial cells are key orchestrators of inflammatory response through the release of both pro-inflammatory cytokines and the upregulation of ICAM-1 adhesion molecules.…”
Section: Epithelial Cellsmentioning
confidence: 99%